A meta-analysis of the association between adherence to drug therapy and mortality. Issue 7557 (21st June 2006) - Simpson, Scot H; Eurich, Dean T; Majumdar, Sumit R; Padwal, Rajdeep S; Tsuyuki, Ross T; Varney, Janice; Johnson, Jeffrey A
Abstract: Objective To evaluate the relation between adherence to drug therapy, including placebo, and mortality. Design Meta-analysis of observational studies. Data sources Electronic databases, contact with investigators, and textbooks and reviews on adherence. Review methods Predefined criteria were used to select studies reporting mortality among participants with good and poor adherence to drug therapy. Data were extracted for disease, drug therapy groups, methods for measurement of adherence rate, definition for good adherence, and mortality. Results Data were available from 21 studies (46 847 participants), including eight studies with placebo arms (19 633 participants). Compared with poor adherence, good adherence was associated with lower mortality (odds ratio 0.56, 95% confidence interval 0.50 to 0.63). Good adherence to placebo was associated with lower mortality (0.56, 0.43 to 0.74), as was good adherence to beneficial drug therapy (0.55, 0.49 to 0.62). Good adherence to harmful drug therapy was associated with increased mortality (2.90, 1.04 to 8.11). Conclusion Good adherence to drug therapy is associated with positive health outcomes. Moreover, the observed association between good adherence to placebo and mortality supports the existence of the "healthy adherer" effect, whereby adherence to drug therapy may be a surrogate marker for overall healthy behaviour.